An Integrated K-Means++–Davies–Bouldin Index Approach for Educational Resource-Based District Clustering: A Case Study of Districts in Surabaya - Subaekti, Hendrik; Hakim, Lutfi; Khaulasari, Hani; Yuliati, Dian (Department of Mathematics, Universitas Negeri Gorontalo, 2026)
Equitable distribution of educational resources is an important prerequisite to ensure that all communities benefit from human resource development. Access to education through the availability of schools and teachers at every level, plays a role in reducing the gap between regions. This study aims to group educational resources at the elementary and junior high school levels in 31 sub-districts of Surabaya City and evaluate the quality of grouping using the Davies–Bouldin Index (DBI). The analysis was carried out using secondary data from the Surabaya City Education Office which included the number of schools, teachers, and students based on education level in each sub-district. The clustering method used is K-Means++, which improves the centroid initialization process to produce more stable clustering. The results of the analysis identified three clusters, namely Development Education Areas (17 sub-districts), Elementary Focused Areas with Limited Junior High Schools (7 sub-districts), and Priority Education Areas (7 sub-districts: Rungkut, Sukolilo, Wonokromo, Sukomanunggal, Genteng, Kenjeran, and Krembangan). The quality of the grouping was validated with a DBI value of 0.752, which indicates a good cluster separation These findings can directly inform the Surabaya City Government in formulating targeted policies for educational equity, especially in teacher placement, student quota adjustment, and infrastructure development.